Characterisation of Dickeya (Erwinia chrysanthemi) strains causing potato blackleg and soft rot in Finland - Laurila, Jaana; Lehtinen, Ari; Ahola, Virpi; Pasanen, Miia; Hannukkala, Asko; Pirhonen, Minna (MTT, 2007)
Contamination of seed tubers with soft rotting enterobacteria is a problem in seed potato production. These bacteria cause blackleg (rotting of potato stems in the field) and soft rot of tubers during storage. In the temperate climate blackleg is caused mainly by Pectobacterium atrosepticum, while P. carotovorum mostly causes rotting of potato tubers. Pathogens in the genus Dickeya (former E. chrysanthemi) were earlier thought to cause both kinds of symptoms in warm and tropical climate, but during the last years they have been reported to spread fast in the Central Europe. To characterise the Finnish soft rot pathogens, bacteria were isolated from diseased potato stems and tuber samples and from river water samples collected from southern and western Finland. The isolated bacteria were verified as Pectobacterium or Dickeya by PCR tests and analysis of 16S 23S rDNA intergenic sequences. All the strains isolated from river samples and 24% of the strains from stems showing blackleg symptoms were identified as Dickeya, whereas only few Dickeya strains were isolated from diseased tubers. Phylogenetic trees based on the 16S and 16S 23S intergenic sequences showed that three different Dickeya groups were present in rivers water, and two of the groups were isolated also from potato samples. One of these groups present in potato and water samples was similar to D. diantihicola, a quarantine pathogen in greenhouse-cultivated ornamentals, but the other groups did not resemble the previously characterised Dickeya species. Field assays suggested that D. dianthicola strains caused symptoms in the majority of the plants and reduced the yield up to 50%. Our results suggest that Dickeya has spread to northern Europe and is more variable than previously anticipated. The results also suggest that some of the highly virulent Dickeya species/strains may be present in rivers and there is a risk that they will spread into potato stocks if contaminated river water is used for irrigation of seed potato fields.
Keywords: Ta; Ka; kasvinsuojelu; kasvitaudit; peruna; perunantyvimätä; Erwinia chrysanthemi; Dickeya spp.; plant protection; Erwinia chrysanthemi